Integrated design at VIDA centre Poland - Weiss, Z.; Konieczny, R.; Diakun, J.; Grajewski, D.; Kowalski, M. (Cranfield University Press, 2009)
The modern design process forces the tight integration of processes connected with the development of the product. All the steps of the design process are based on geometrical models created in CAD systems. The geometry of the product is used for programming of the virtual environment of the product, its behaviour, manufacturing and so on. It is necessary to remember that the integrated design process needs special skills and knowledge from engineers. The authors of this paper presented a brief description of the VIDA Centre at Poznań University of Technology, its structure and skills in the area of integrated design. Couples of examples of projects realized at VIDA Centre’s environment as integrated design of products are described as well.
Organised by: Cranfield University
Keywords: Product Development; Integrated Design; VIDA Centre’s environment; VIDA skills in integrated design